Boneka Ekspresi Sebagai Alternatif Pembelajaran Afeksi pada Siswa Autis - Tyas Martika Anggriana; Faravika Helmastuti; Kovneliarum Dianggi; , Chindi Mileniar Maghfiroh (Program Studi Pendidikan Profesi Guru, Universitas Sarjanawiyata Tamansiswa Yogyakarta, Indonesia., 2022)
One of the learning barriers experienced by students with autism is affective barriers. Students with autism generally find it difficult to understand everything related to attitudes and values and express their emotions in an appropriate way. This study aims to systematically explain the use of expression dolls as an alternative to learning affection for autistic students. This research is library research or literature research conducted by utilizing library sources to obtain research data. Researchers search for, collect, organize and analyze scientific papers that have been collected. The results of data analysis are then used as a basis for drawing conclusions. Based on the literature review, it can be concluded that expression dolls are dolls whose faces have various emotional expressions. During the learning process, teachers can use expression dolls along with the application of storytelling and guessing expressions methods. Expression puppet media is categorized as a form of visual learning media that is expected to be effective for students with autism. Through expression dolls, students with autism are expected to improve their ability to express their emotions naturally.